Evaluation of the New York City Police Cadet Corps, 1986-1989 - Pate, Antony ([Verlag nicht ermittelbar], 1995)
The purpose of this study was to examine whether the Police Cadet Corps program in New York City had achieved its goal of improving the police force through additional training of applicants with higher education. The evaluation of the program was designed to answer questions such as (1) How was the program recruitment implemented, and with what success? (2) What were the role-related perceptions and attitudes of the cadets and how did they differ, if at all, among different types of cadets and from those of the members of the latest recruit class? (3) How, if at all, did the program experience affect the cadets' perceptions and attitudes? and (4) How did the attitudes and perceptions of cadets compare to non-cadet recruits with and without some college education in the same academy class? Four cohorts of cadets were asked to complete several different questionnaires throughout the course of the program, which culminated in graduation from the police academy. Two sets of non-cadet recruits from the academy were also included in the research. Major variables in the data collection detail reasons for entry into the police department, opinions regarding police, and perceptions and attitudes toward the police cadet program. Some questionnaires also provided information on demographic characteristics of the cadets (race, sex, marital status, military service and branch, highest level of education, family income, and year of birth). The unit of observation is the New York City police cadet.